Carbon Footprint of Polypropylene Product in Iranian Petrochemical Industry - Sara Safi Jahanshahi; Ahmad Sherafati; Hossein Vahidi (Environmental Energy and Economic Research)
This study presents a comprehensive carbon footprint analysis of polypropylene production within an Iranian petrochemical facility, employing a broad scope that encompasses all relevant processes across the entire factory, rather than focusing solely on the polypropylene production unit. Utilizing a life cycle assessment (LCA) approach aligned with ISO standards, the research quantifies greenhouse gas (GHG) emissions from each production stage, including raw material processing, energy generation, and waste management, to provide a holistic view of environmental impacts. Key findings reveal that energy-intensive units, particularly power generation and steam production, are the primary contributors, accounting for over 90% of total emissions. The study's broadened scope offers a more accurate depiction of the facility's environmental burden and highlights significant areas for emission reductions. By identifying these critical areas, the research not only advances our understanding of polypropylene's environmental profile but also suggests targeted interventions such as the adoption of renewable energy sources and efficiency improvements. This analysis not only sets a benchmark for future environmental assessments within the industry but also serves as a crucial tool for policymakers and industry leaders aiming to implement more sustainable manufacturing practices. The findings underscore the importance of expanding the system boundaries in carbon footprint assessments to include all associated processes for a more accurate and actionable environmental impact evaluation.